1975
DOI: 10.1180/minmag.1975.040.309.12
|View full text |Cite
|
Sign up to set email alerts
|

Identification of iron-containing impurities in natural kaolinites using the Mössbauer effect

Abstract: SUMMARY. Two clay samples originating in the kaolinized granite area near St. Austell, Cornwall, have been examined by MSssbauer spectroscopy. The iron-containing impurity in the sample with a red discoloration (sample A) has, by measurement of the hyperfine magnetic field, been identified as hematite. In the case of sample B, which was yellow in colour, preliminary MSssbauer work indicated fi-FeOOH as the impurity, but detailed measurements of hyperfine field and N6el temperature, when compared with similar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 15 publications
3
13
0
Order By: Relevance
“…On cooling a sample of the uncontaminated sediment the spectral area of the ferric doublet was decreased, and a magnetic component appeared that formed about 50% of the total area at 77~ and 4.2~ (Figure 2). The hyperfine field value at 4.2~ of 499 kOe is in better agreement with that expected for goethite, 506 kOe (van der Kraan and van Loef, 1966), than that for /3-FeOOH, 470 kOe (Hogg et al, 1975). Since no magnetic component in the room temperature spectrum was found, it is likely that the goethite is present as finely divided particles (Shinjo, 1966;van der Kraan and van Loef, 1966;Govaert et al, 1977), although the possibility that it contains some substituted aluminum cannot be ruled out on the basis of the field values (Bigham et al, 1978).…”
Section: Resultssupporting
confidence: 67%
“…On cooling a sample of the uncontaminated sediment the spectral area of the ferric doublet was decreased, and a magnetic component appeared that formed about 50% of the total area at 77~ and 4.2~ (Figure 2). The hyperfine field value at 4.2~ of 499 kOe is in better agreement with that expected for goethite, 506 kOe (van der Kraan and van Loef, 1966), than that for /3-FeOOH, 470 kOe (Hogg et al, 1975). Since no magnetic component in the room temperature spectrum was found, it is likely that the goethite is present as finely divided particles (Shinjo, 1966;van der Kraan and van Loef, 1966;Govaert et al, 1977), although the possibility that it contains some substituted aluminum cannot be ruled out on the basis of the field values (Bigham et al, 1978).…”
Section: Resultssupporting
confidence: 67%
“…6). Unless the particle size of the iron oxides is extremely small, in which case they could be paramagnetic, the occurrence of well crystallized ferric components is also excluded (Janot et al, 1973;Hogg et al, 1975;Bonnin et al, 1982;Fysh et al, 1983).…”
Section: Mossbauer Spectroscopymentioning
confidence: 99%
“…Hogg et al (1975) noted the importance of distinguishing between kaolinite structural iron and iron in impurities, and fine particles of hematite and goethite were identified by them and Janot et al (1973). Jefferson et al (1975) found that the nonstructural iron was included in a non-crystalline gel, coating the surface of the kaolinite flakes, or in a fine coating of goethite.…”
mentioning
confidence: 96%
“…The considerable number of studies employing ESR techniques have recently been reviewed by Hall (1980). Hogg et al (1975) noted the importance of distinguishing between Fe present within the kaolinite structure and Fe located in the impurities such as mica and iron oxides/oxyhydroxides which are common in kaolin ores. Both they and Janot et al (1973) identified fine particles of hematite and goethite in kaolin samples.…”
Section: The Nature Of the Iron Associated With Kaolinmentioning
confidence: 99%